Intraosseous stability of dental implants in free revascularized fibula and iliac crest bone flaps. Issue 12 (December 2016) - Möhlhenrich, Stephan Christian; Kniha, Kristian; Elvers, Dirk; Ayoub, Nassim; Goloborodko, Evgeny; Hölzle, Frank; Modabber, Ali
Abstract: The aim of this study was to investigate the influence of two different microvascular reanastomized bone transplants on primary (PS) and secondary stability (SS) of dental implants. Totally 96 implants (Bone Level, Institut Straumann AG, Basel, Switzerland) were inserted in fibula (n = 50) and iliac crest (n = 46) in mean of 97.7 SD 75.6 weeks after performing reconstructive surgery. For measuring PS and SS the resonance frequency (RFA) analysis was used in mesiodistal and vestibulo-oral direction to quantify the implant stability quotient (ISQ). Mean values (ISQ) for PS in fibula was about 79.48 SD 2.41 and in iliac crest 61.10 SD 3.34 as well as SS in fibula was about 75.59 SD 5.10 and in iliac crest 73.63 SD 5.34. Statistically significant differences between both flaps were found for PS in mesiodistal and vestibulooral direction (p < 0.001). Between the primary and SS a significant decrease was recognized in fibula flap (p < 0.01) as well as an increase in iliac crest flap (p < 0.001). Statistically no difference was found between both bone flaps for SS (p = 0.076). The implant stability in fibula and iliac crest flap after osseointegration is similar to each other. Therefore, it is not important for choosing the suitable donor side. Highlights: Primary stability is higher in microvascular fibula than iliac crest flap. In the vestibulooral direction, primary stability is higher than mesiodistal. Implant stability decreases in fibula and increases in iliac crest graft. No differences for implant stability between both flaps after osseotinegration.